2022
DOI: 10.18615/anadolu.1130026
|View full text |Cite
|
Sign up to set email alerts
|

Erzincan İli Merkez İlçesi Sığırcılık İşletmelerinde Barınakların Yapısal Özellikleri ve İşletmecilerin Öğrenim Durumlarıyla İlişkileri

Abstract: Bu araştırma, Erzincan ili merkez ilçesine bağlı köy ve beldelerde bulunan sığırcılık işletmelerindeki sığır barınaklarının yapısal özelliklerini, işletme sahiplerinin öğrenim durumlarını, problemlerini ve çözüm önerilerini ortaya koymak amacıyla yapılmıştır. Ayrıca, barınak yapısal özellikleri ile işletme sahiplerinin eğitim düzeyleri arasındaki ilişkilerde analiz edilmiştir. Bu amaçla, merkez ilçede bulunan 2003 işletmeden basit tesadüfi örnekleme yöntemiyle rastgele seçilen 401 adet işletme sahibiyle yüz yü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Mundan et al (2018) in their study in Şanlıurfa, it was determined that 17.5% of the barns were tie-stall, 82.5% of them were tie-stall type, and free-stall barn system was used in all of them. Their study in Özsağlıcak and Yanar (2022) found that 95.0% of their research had tie-stall barns, 4.8% had free tie-stall barns, and 0.3% had loose barns. 50.6% stated that stone (22.7%), adobe (12.6%), brick (11.6%), pumice (2.2%), and wood (0.3%) were used.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Mundan et al (2018) in their study in Şanlıurfa, it was determined that 17.5% of the barns were tie-stall, 82.5% of them were tie-stall type, and free-stall barn system was used in all of them. Their study in Özsağlıcak and Yanar (2022) found that 95.0% of their research had tie-stall barns, 4.8% had free tie-stall barns, and 0.3% had loose barns. 50.6% stated that stone (22.7%), adobe (12.6%), brick (11.6%), pumice (2.2%), and wood (0.3%) were used.…”
Section: Resultsmentioning
confidence: 97%
“…Delebe (2022), in his study in Şanlıurfa province, stated that the rate of those who keep each calf in a separate compartment is 4.96%, and the rate of those who keep them freely as a group in a particular place is 95.03%. In the study conducted by Özsağlıcak and Yanar (2022), in the province of Erzincan, 60.3% of the holdings had calves in a separate group section in the same barn, 11.7% in the same barn with the mother, 15.9% in the same barn in individual calf sections and 12% in the same barn. They reported that they were reared in individual calf huts in separate buildings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when juxtaposed with the study by Özsağlıcak and Yanar (2022), which focused on cattle enterprises, a distinct pattern emerges. In the present study, 95.0% of cattle enterprises reported closed barns, while 4.8% and 0.3% had semi-open and open barns, respectively.…”
Section: Animal Presence Of Enterprisesmentioning
confidence: 93%
“…In a study conducted in Erzincan province, it was reported that in 47.4% of the enterprises, milking is done manually, in 47.1%, mobile milking machines are used, and in 5.5%, milking is carried out in milking units (Özsağlıcak & Yanar, 2022).…”
Section: Milkingmentioning
confidence: 99%